2013
DOI: 10.1109/lcomm.2013.092813.131480
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Hybrid ARQ System Using Turbo Product Codes with Hard/Soft Decoding

Abstract: The bit error rate (BER) performance of turbo product codes (TPC) has been considered extensively in the literature. However, other performance metrics such as throughput can be more informative in particular systems. In this letter, the throughput performance of hybrid automatic repeat request (HARQ) is considered using TPC with iterative hard and soft decision decoding. Monte Carlo simulation and semi-analytical solutions are developed to evaluate the throughput of HARQ-TPC system for a wide selection of cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
(29 reference statements)
0
23
0
Order By: Relevance
“…In this project, an adaptive TPC HARQ scheme with packet combining is proposed to maximize system throughput based on the channel condition. Preliminary results show that system complexity and power consumption can be reduced while maintaining the system throughput unchanged [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this project, an adaptive TPC HARQ scheme with packet combining is proposed to maximize system throughput based on the channel condition. Preliminary results show that system complexity and power consumption can be reduced while maintaining the system throughput unchanged [5].…”
Section: Introductionmentioning
confidence: 99%
“…The adaptation process is performed to maximize the system throughput by changing the codeword size and code rate based on the channel condition. Based on our evaluation of the T-HARQ system, we observed that system complexity and power consumption can be reduced while maintaining the system throughput unchanged [5]. In the second part of the PhD project, we plan to find out an optimum power assignment per retransmission for the T-HARQ system such that for a given throughput value the total consumed power is minimized.…”
Section: Introductionmentioning
confidence: 99%
“…In our work in [12] a power optimization algorithm is proposed to minimize the transmit energy under throughput constraints. The main motivation for adopting this approach is the unique behavior of several HARQ systems where the throughput varies in a staircase manner as a function of the signal-to-noise ratio (SNR) [13]- [16]. The staircase behavior of the throughput implies that the transmit power can be controlled eruptively to minimize the total transmit energy while maintaining the throughput unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…In the second phase, the receiver verifies if the FEC process was successful, and then sends a message to the transmitter to retransmit the packet if the FEC process was unsuccessful; otherwise, the message informs the transmitter to send the next packet in the transmitter buffer. In general, most of the work reported in the literature performs the bit error correction and packet error detection (PED) as two independent processes where the FEC is implemented at the Physical Layer (PHY) while the PED is performed at the Data Link Control (DLC) layer [5], [6]. Because the FEC and PED are implemented at two different layers, the interaction between the two FEC and PED operations is considered as a cross-layer cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…The PED is usually performed using cyclic redundancy check (CRC) codes [5], [6]. The generic implementation of the CRC process is based on a linear feedback shift register (LFSR) that performs the polynomial division process of the serial data input.…”
Section: Introductionmentioning
confidence: 99%